Bangladesh : Joint Staff Assessment of the Poverty Reduction Strategy Paper Status Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents a status report on Bangladesh's Poverty Reduction Strategy Paper. Prudent macroeconomic management has contributed to robust growth and moderate inflation. External conditions have improved with a significant buildup in international reserves. The exchange rate has remained competitive in real effective terms, and rigidities in interest rates have been reduced. The authorities have also pursued tax administration and banking reforms, with implementation broadly on track under the Poverty Reduction and Growth Facility program.